Preemptive nebulized ketamine for pain control after tonsillectomy in children: randomized controlled trial - Abdel-Ghaffar,Hala S. (2019)
Abstract Objectives The administration of ketamine as nebulized inhalation is relatively new and studies on nebulized ketamine are scarce. We aimed to investigate the analgesic efficacy of nebulized ketamine (1 and 2 mg.kg-1) administered 30 min before general anesthesia in children undergoing elective tonsillectomy in comparison with intravenous ketamine (0.5 mg.kg-1) and saline placebo. Methods One hundred children aged (7-12) years were randomly allocated in four groups (n = 25) receive; Saline Placebo (Group C), Intravenous Ketamine 0.5 mg.kg-1 (Group K-IV), Nebulized Ketamine 1 mg.kg-1 (Group K-N1) or 2 mg.kg-1 (Group K-N2). The primary endpoint was the total consumption of rescue analgesics in the first 24 h postoperative. Results The mean time to first request for rescue analgesics was prolonged in K-N1 (400.9 ± 60.5 min, 95% CI 375.9-425.87) and K-N2 (455.5 ± 44.6 min, 95% CI 437.1-473.9) groups compared with Group K-IV (318.5 ± 86.1 min, 95% CI 282.9-354.1) and Group C (68.3 ± 21.9 min, 95% CI 59.5-77.1; p < 0.001), with a significant difference between K-N1 and K-N2 Groups (p < 0.001). The total consumption of IV paracetamol in the first 24 h postoperative was reduced in Group K-IV (672.6 ± 272.8 mg, 95% CI 559.9-785.2), Group K-N1 (715.6 ± 103.2 mg, 95% CI 590.4-840.8) and Group K-N2 (696.6 ± 133.3 mg, 95% CI 558.8-834.4) compared with Control Group (1153.8 ± 312.4 mg, 95% CI 1024.8-1282.8; p < 0.001). With no difference between intravenous and Nebulized Ketamine Groups (p = 0.312). Patients in intravenous and Nebulized Ketamine Groups showed lower postoperative VRS scores compared with Group C (p < 0.001), no differences between K-IV, K-N1 or K-N2 group and without significant adverse effects. Conclusion Preemptive nebulized ketamine was effective for post-tonsillectomy pain relief. It can be considered as an effective alternative route to IV ketamine.